Evaluation and Identification of the Effective Factors on the Improvement of Walkability in the Neighborhoods of Rasht City - naeim ghaffari hashjin; Yousef Jahanzamin (Lowland Technology International, 2021)
this study aims to identify and explain the effective factors on the improvement of walkability in urban neighborhoods. The nature of this study is applied in terms of objective and is analytical-descriptive in terms of method; furthermore, this study is a cross-section study in terms of time. The measurement tools in this study are the researcher-made questionnaire including questions related to the personal characteristics of the subjects and 40 indicators related to walkability. 400 questionnaires were distributed among the neighborhood’s residents and completed using a convenient sampling method and after the initial investigation, 387 questionnaires were used to analyze the data. data were evaluated using the Exploratory Factor Analysis Method. using the factor analysis, seven factors with the special value higher than 1 were extracted for the research items that after the factor rotation using the varimax method, the variables related to the improvement of walkability were classified into 7 factors; the factors obtained from the factor analysis, considering its constituent items, are called presence, surveillance, social, node and pause, economical, legibility, infrastructural, and physical factors, respectively. In the end, given the results of the research, some suggestions were recommended to improve the walkability in the urban neighborhood.